INCLUSIVE EDUCATION POLICIES AND TRIBAL GOVERNANCE: A CASE STUDY OF NORTHEAST INDIA. - 1. Himan Jyoti Bora , 2 . Dr. Riju Sarma , 3. Dr. Subhrangshu Dhar (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The article examines the intersection of inclusive education policies and tribal governance in the context of Northeast India, with a focus on the challenges and opportunities in promoting educational equity for indigenous communities. Despite numerous national frameworks like the RTE Act, tribal communities in the region face persistent educational inequalities driven by socio-economic, cultural, and geographical barriers. The role of tribal governance, customary laws, and the interaction between state policies and tribal authorities is explored to understand how local governance structures influence education. Government initiatives and the contributions of NGOs are analyzed, highlighting their impact on improving access to education for tribal children. The study identifies key challenges such as inadequate infrastructure, language barriers, and limited local participation in policymaking. Opportunities for strengthening the role of tribal governance in education policy implementation and promoting culturally responsive education models are discussed. The article concludes with policy recommendations aimed at enhancing inclusive education for tribal communities through better integration of tribal governance, local participation, and sustainable education models that respect cultural diversity.